Constructive Communication in International Teams An Experience-Based Guide - iCom Team (Waxmann, 2014)
While communicating has become much easier with new technologies, it hasn't necessarily become more successful. The complexity of communication has increased - and so have the pitfalls. Want to be one step ahead of them? Based on the principles of humanistic management, this book offers a new angle on how effective communication can make a difference in your working life. The international team of authors - computer scientists, company founders, start-up managers, researchers in communication and psychology and educators - bridges the gap between universities and the business world. They elaborate new paths to communication, leadership, and knowledge management, using real cases and research-based insights. This book doesn't just offer simple "How-to-solutions", it aims at something more substantial: professional development and personal growth. It is about finding inspiration and sharing it with others